2016
DOI: 10.2147/tcrm.s116603
|View full text |Cite
|
Sign up to set email alerts
|

The association of serum gamma-glutamyl transpeptidase level and other laboratory parameters with blood pressure in hypertensive patients under ambulatory blood pressure monitoring

Abstract: BackgroundHypertension is a very important cause of morbidity and mortality. Serum gamma-glutamyl transpeptidase (GGT) is a biomarker of oxidative stress and associated with increased risk of hypertension and diabetes. The aim of this study was to evaluate the association of serum GGT level, which is an early marker of inflammation and endothelial dysfunction, with the deterioration of the diurnal rhythm of the blood pressure.MethodsA total of 171 patients with hypertension were included in this study. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…GGT is responsible for the extracellular degradation of the antioxidant glutathione, resulting in reactive oxygen radicals [41]. Increased levels of GGT have been shown to be associated with subclinic inflammation [42], CVS and metabolic diseases [43] [44]. It has been shown that cyclosporine hepatotoxicity is less in vildagliptin-given rats and has a positive effect on serum GGT [45].…”
Section: Ggtmentioning
confidence: 99%
“…GGT is responsible for the extracellular degradation of the antioxidant glutathione, resulting in reactive oxygen radicals [41]. Increased levels of GGT have been shown to be associated with subclinic inflammation [42], CVS and metabolic diseases [43] [44]. It has been shown that cyclosporine hepatotoxicity is less in vildagliptin-given rats and has a positive effect on serum GGT [45].…”
Section: Ggtmentioning
confidence: 99%